Reliability Assessment of Bored Pile Foundations using a Probabilistic Approach based on SPT Data: - - Anastasia Dayinta Adella; Sumiyati Gunawan (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2026)
Deep foundations perform an important role in supporting structural loads and transferring them to deeper and stronger soil layers. The soil parameters used in geotechnical design practice are commonly obtained from field tests, such as the Standard Penetration Test (SPT), which exhibit a high degree of uncertainty due to variations in soil conditions, testing procedures, and data interpretation. These uncertainties significantly influence the reliability of deep foundation design. Such study aims to evaluate the reliability of bored pile foundations and determine their safety level based on SPT data from five boreholes at various depths using a probabilistic approach. The Monte Carlo simulation method was employed to model the variability of soil strength, determine the reliability index (β), and estimate the probability of failure (Pf). The analysis results show that although the deterministic safety factor (SF ≥ 1) indicates a safe condition, the probabilistic analysis reveals that the system still has a failure probability of approximately 48% and a reliability level of only about 52%, indicating a marginal state. The reliability index limit (β = 0.05) serves as a minimum threshold separating safe and unsafe conditions. Increasing the pile diameter significantly improves the reliability index and reduces the failure probability, demonstrating a strong correlation between design parameters and reliability performance. Overall, the findings highlight that the deterministic approach alone cannot adequately capture soil parameter uncertainty, and reliability-based design (RBD) provides a more realistic and quantitative framework for assessing foundation safety in geotechnical engineering.